PERSPECTIVES OF UNIVERSITY STUDENTS OF THE CARPATHIAN BASIN ON THE LOSS OF TEACHERS’ AUTHORITY: Received: 3rd February 2025, Revised: 20th March 2025, 2nd April 2025, Accepted: 23rd April 2025, Date of Publication: 15th July 2025 - Adrián Žemlička; Dávid Szabó L; Klaudia Pauliková; Eva Tóthová Tarová (PUPIL: International Journal of Teaching, Education and Learning, 2025)
The study examines the perceptions of university students in Hungarian-language institutions in several countries in the Carpathian basin with regards to teacher authority and the loss of authority. The theoretical background portrays the requirements on an ideal teacher, their characteristic features, as well as the evolution of these attributes over time. Expectations for teachers are examined within three dimensions, with the dimension addressing teacher personality traits being dominant in this study. Utilizing the Big Five personality model, each trait is perceived as a spectrum. The study encompasses responses from a total of 1037 university students to a questionnaire, with data processed and analysed via the statistical software SPSS. The findings of the study indicate that the most characteristic features of an authoritative teacher are being strict, respectful, firm, kind, and helpful. The loss of authority, on the other hand, is most likely linked to being disrespectful, unfair, and condescending towards their students.